2021
DOI: 10.1021/acsomega.0c05936
|View full text |Cite
|
Sign up to set email alerts
|

Organosolv Fractionation of Walnut Shell Biomass to Isolate Lignocellulosic Components for Chemical Upgrading of Lignin to Aromatics

Abstract: Renewable carbon sources are a rapidly growing field of research because of the finite supply of fossil carbon. The lignocellulosic biomass walnut shell (WS) is an attractive renewable feedstock because it has a high lignin content (38–44 wt %) and is an agricultural waste stream. Lignin, a major component of lignocellulosic biomass that is currently a waste stream in pulping processes, has unique potential for chemical upgrading because its subunits are aromatic. In the interest of improving the sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…We also compared the above approach to one where several organosolv methods were used to separate lignins from the high-S poplar biomass prior to the hydrogenolysis to monomers. 30,[35][36][37][38][39] However, the drawbacks of these methods are obvious given that they require extra usage of solvents, time, and energy. 31,[38][39][40][41] More importantly, the properties of organosolv lignins are often altered during these fractionation treatments, including re-condensation reactions forming unnatural and recalcitrant C-C bonds.…”
Section: Discussionmentioning
confidence: 99%
“…We also compared the above approach to one where several organosolv methods were used to separate lignins from the high-S poplar biomass prior to the hydrogenolysis to monomers. 30,[35][36][37][38][39] However, the drawbacks of these methods are obvious given that they require extra usage of solvents, time, and energy. 31,[38][39][40][41] More importantly, the properties of organosolv lignins are often altered during these fractionation treatments, including re-condensation reactions forming unnatural and recalcitrant C-C bonds.…”
Section: Discussionmentioning
confidence: 99%
“…within the organosolv treatment of biomass under acidic conditions, to suppress the repolymerization of the solubilized lignin and hemicellulose intermediates by formation of relatively stable acetal structures. [508][509][510][511][512][513][514][515] AAF is carried out in acidied aqueous mixtures of aprotic organic solvents (e.g. dioxane), at temperatures in the range of 80-120 °C.…”
Section: Aldehyde-assisted Fractionationmentioning
confidence: 99%
“…In their work, Nishide et al investigated various parameters affecting the organosolv process, such as different solvents, catalysts, and process temperatures. [79] They found that in the environment catalyzed by alcoholic acids, an increase in temperature leads to a decrease in polydispersity and average molecular weight. A temperature-dependent trend is also observed by Yao et al [80] They isolated organosolv lignins from Broussonetia papyrifera at 150, 160, 170 and 180 °C, respectively, and examined their structural differences.…”
Section: Influence Of Process Temperaturementioning
confidence: 99%